The Euro-dollar system : practice and theory of international interest rates - Einzig, Paul; Scott-Quinn, Brian (London : Macmillan, 1977)
This book attempts to highlights the early stages of the development of the Euro-dollar system. It outlined most of the far-reaching consequences of the Euro-dollar system at a time when many thought it to be a transitory phenomenon. It also showed that the expansion of the Euro-dollar system could have only a trivial impact on the U.S. money supply, while others worried first that it could lead to a sizeable leakage of bank reserves from the United States and later, when U.S. banks became important borrowers of Euro-dollars, that it could lead to an explosive expansion of U.S. bank reserves. The author argued that Regulation Q restrictions on bank deposits in the United States were not a necessary condition for the expansion of the Euro-dollar system, at a time when many regarded them as a crucial part of the explanation for the growth of the Euro-dollar system.
Includes index.
usc 11/06/18
Loans
Keywords: Euro-dollar market; Interest rates; Banks and banking, International; Foreign exchange